Pemberian Jenis Atraktan yang Berbeda Terhadap Tingkat Komsumsi Pakan dan Pertumbuhan Ikan Kakap Putih Lates calcarifer - Rafika Mulia; Tri Yulianto; Rika Wulandari (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
The administration of attractant aims to stimulate the appetite of white snapper Lates calcarifer to increase feed consumption and growth. This research was conducted in July - August 2020 for 42 days at the Marine Product Laboratory, Faculty of Marine Sciences and Fisheries, Raja Ali Haji Maritime University, Riau Islands Province. The method used is experimental with Complete Randomized Design (RAL) with 4 treatments and 3 repeats which Control is feed without attractant, treatment A (feed + glutinous squid flour), treatment B (feed + fish meal attractant), treatment C (feed + glutinous shrimp flour rebon). The results obtained in the response of fish and the best amount of feed consumption is treatment C of 0.45% for the amount of feed consumption is 73.50% and at the growth of the best result is the absolute weight of B treatment 11.22%, absolute length 3.34% and survival of 91.67%.